Meningkatkan Hasil Belajar Matematika Materi Bangun Ruang melalui Penggunaan Media Tiga Dimensi pada Siswa Kelas V SDN Cipondoh 4 Kota Tangerang - Unaenah, Een; Manjaya, Raja Ashabul Humayah (Lembaga Yasin AlSys, 2023)
The purpose of this study is to improve mathematics learning outcomes of space building materials through the use of three-dimensional media in students. Based on the results of research and discussions that have been carried out, the following conclusions can be drawn: 1) The use of three-dimensional media in learning to build space in grade V students of SD N Cipondoh 4 Tangerang can improve student learning outcomes. This is evidenced by the increase in class average scores and the percentage of student completeness at each stage of the study. In the precycle stage, the average score of students reached 61.14 and in cycle I it increased to 71 then increased again in cycle II to 81. While the percentage of student completeness in the pre-action stage only reached 51%, while in the first cycle student completeness increased to 71%, then increased again in the second cycle to 94. 2) The use of three-dimensional media in building space learning in grade V V SD N Cipondoh 4 Tangerang students can improve the quality of the learning process. This is evidenced by the increase in teacher activity during the learning process from cycle I by 83% to 90% in cycle II with a very good category.